Persuasive Technology - Oinas-Kukkonen, H. (Springer, 2017)
Until recently, mostsoftwareapplications and technologiesweredeveloped wi- out much thought to how they in?uenced their users. This perspective is cha- ing.Today,industryexpertsandacademicsareembracingapurposefulapproach to persuasive design. In an industry context, designing for persuasion is bec- ingessentialforsuccess.Inacademicsettings,thestudyofpersuasivetechnology illuminates the principles that in?uence and motivate people in di?erent aspects of their lives. Persuasive technology is rapidly growing into a major discipline, sometimes referred to as captology or the study of computers as persuasive technologies. The previous Persuasive conferences held in Eindhoven (2006) and Stanford (2007) were infused with an energetic spirit and a large attendance, including representatives from both academia and industry. Persuasive 2008, hosted in Oulu, Finland in early June, was jointly or- nized by the University of Oulu, Finland and Aalborg University,Denmark. The northern location of Oulu, only some two hours away from the Arctic Circle, o?ers sunlight 24 hours a day, allowing conference participants to experience the midnight sun. This three-day conference placed persuasive technology on a ?rm scienti?c footing with an emphasis on social, psychological, rhetorical and ethical issues. Featuring full and short papers, posters and panels, Persuasive2008 highlighted new knowledge in the understanding and design of persuasive technology. The event brought together researchers, practitioners, and industry professionals - terested in this important new ?eld. Research themes of the conference included motivationaltechnology,persuasivegames,smartenvironments,Web2.0, mobile persuasion, well-being and health behavior. In addition, attendees and part- ipants explored the theory and ethics of persuasive technology, social and - ganizational issues, business models for persuasive systems, and conceptual and theoretical approaches.